MicroRNA-31 Reduces the Motility of Proinflammatory T Helper 1 Lymphocytes - Bardua, Markus; Haftmann, Claudia; Durek, Pawel; Westendorf, Kerstin; Buttgereit, Antje; Tran, Cam Loan; McGrath, Mairi; Weber, Melanie; Lehmann, Katrin; Addo, Richard Kwasi; Heinz, Gitta Anne; Stittrich, Anna-Barbara; et al. (Frontiers in Immunology, 2018)
Proinflammatory type 1 T helper (Th1) cells are enriched in inflamed tissues and contribute to the maintenance of chronic inflammation in rheumatic diseases. Here we show that the microRNA- (miR-) 31 is upregulated in murine Th1 cells with a history of repeated reactivation and in memory Th cells isolated from the synovial fluid of patients with rheumatic joint disease. Knock-down of miR-31 resulted in the upregulation of genes associated with cytoskeletal rearrangement and motility and induced the expression of target genes involved in T cell activation, chemokine receptor– and integrin-signaling. Accordingly, inhibition of miR-31 resulted in increased migratory activity of repeatedly activated Th1 cells. The transcription factors T-bet and FOXO1 act as positive and negative regulators of T cell receptor (TCR)–mediated miR-31 expression, respectively. Taken together, our data show that a gene regulatory network involving miR-31, T-bet, and FOXO1 controls the migratory behavior of proinflammatory Th1 cells.